Kelayakan Media Colored Smart Cube Untuk Menstimulasi Pengenalan Warna Di Kelompok A Tk Bunga Bangsa Mojodadi - Aida Fitriati; Mardi Widodo (Jurnal Pendidikan Indonesia, 2022)
One of the aspects of development that needs to be developed and is very important in the world of the future is the cognitive aspect. In developing this aspect, not only by providing subject matter but the use of media also greatly affects it. Therefore, educators are required to be more creative in the development of learning media. This study aims to produce a decent Colored Smart Cube media and is able to stimulate the ability to recognize colors in group A students more precisely at the age of 4-5 years. The method used by researchers in this case is (Research and Development) by taking 6 stages including: potential problems, data collection, product design, design validation, product revision and trials. For product validation, it is carried out by five validators, namely two material expert validators and three media expert validators with the results of media expert data analysis an average of 4 with a percentage of 80% while the results of material expert data analysis average 3.7 with a percentage of 75%. It can be concluded that the Colored Smart Cube media in the criteria is feasible to use or apply in early childhood learning, especially in terms of color recognition.